2010
DOI: 10.21273/horttech.20.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Cold Tolerance of Container-grown Green Ash Trees Is Influenced by Nitrogen Fertilizer Type and Rate

Abstract: A study was conducted to determine whether nitrogen (N) application rate and fertilizer form are related to cold tolerance of buds and stems using container-grown ‘Summit’ green ash (Fraxinus pennsylvanica) trees. Trees were grown with different rates of N from either urea formaldehyde (UF) or a controlled-release fertilizer (CRF) containing ammonium nitrate during the 2006 growing season; and growth, N and carbon (C) composition, and cold tolerance were evaluated in Oct. 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Low levels of water stress in containers can promote early nutrient mobilization in the fall and spring (Sanz-Pérez et al, 2009). Delayed nutrient mobilization could also reduce cold-hardiness and result in tissue damage and loss of biomass over the winter (Colombo et al, 2003;Scagel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of water stress in containers can promote early nutrient mobilization in the fall and spring (Sanz-Pérez et al, 2009). Delayed nutrient mobilization could also reduce cold-hardiness and result in tissue damage and loss of biomass over the winter (Colombo et al, 2003;Scagel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although the damage is on low level, REL-data for the loaded plants are higher than for the non-loaded ones being significant for the exponentially loaded plants at -8°C. This might be due to the higher N-concentration in this year's shoots of these plants ( the results concerning the influence of high fertilization on frost hardiness are not consistent; both an increase (Rikala and Repo, 1997) and a decrease (Scagel et al, 2010) are reported. Concerning nutrient loading, Miller et al (1995) in Timmer and Aidelbaum (1996) found for white spruce no difference between conventionally and exponentially loaded plants.…”
Section: Early and Late Frost Experimentsmentioning
confidence: 74%
“…Chemical protection for crops or trees includes the use of different products that can be classified as conventional agrochemicals (e.g. nutrients or fertilizers, such as nitrogen (Scagel et al., 2010; Toca et al., 2018), potassium (Centinari et al., 2016; Ma et al., 2019), and calcium (Marosz & Nogowska, 2018; Vega et al., 1996)), biostimulants or growth regulators (Dwyer et al., 1995; Tsipouridis et al., 2006; Yang et al., 2019), pesticides (Robinson et al., 2015; Tsipouridis et al., 2006), and products whose main objective is to protect the crop or plant against freezing (Anderson, 2012; Francko et al., 2008, 2011; Hernández et al., 2016; Starkutė et al., 2017).…”
Section: Chemical Protection Methodsmentioning
confidence: 99%
“…nitrogen, potassium, and calcium) to protect crops against low‐temperature stress have been evaluated; however, the effectiveness of nutrients has been variable and depends on the kind of nutrient (Table 2). Among evaluated nutrients, nitrogen exhibited a negative or marginal crop protective effect (Scagel et al., 2010; Toca et al., 2018), which is probably ascribable to plants receiving nitrogen at greater doses than required, which increases their growth (biomass and stems) and, consequently, their susceptibility to stress, which decreases their low‐temperature tolerance. This is possible because under nitrogen excess, plants employ non‐structural carbohydrates for their growth, especially under conditions of stress, hence protection gave by those carbohydrate is reduced (Huber & Watson, 1974; Palacio et al., 2007).…”
Section: Chemical Protection Methodsmentioning
confidence: 99%
See 1 more Smart Citation